A study on the relationship between financial management and loan repayment / Suhayl Azmin Adli - Adli, Suhayl Azmin (Faculty of Business and Management, 2019)
Malaysia is without a doubt a country that is recognizable as a developing country, but as the country is thriving towards success, there are some issues that arise that might become as a blockage for Malaysia to be a developed country. One of the issues is that the country is facing hardships in settling its debt, as reported by Bernama "Moody's investors' services", New Straits Times (May 14, 2018). Furthermore, the citizens of Malaysia have a big outstanding balance of debt towards their government. To narrow the scope, I would like to focus on the unpaid students' loan. Students that are still pursuing their studies and those who have already finished their studies have problems in settling their debt. As said by Tun Dr. Mahathir, Malaysia Prime Minister, unpaid student loan amounting to RM39 billion nearly same as IMDB debt reported by Hazlin Hassan, New Straits Time (August 1 1, 2018). In this study, my focus would be on the relationship between financial management behaviour and loan repayment. The issue here is does the factor financial management behaviour would directly affect the loan repayment decisions of an individuals. As reported by Dr Marimuthu Nadason in the Free Malaysia Today (August 27, 2018), said that Malaysian citizen are in serious financial problems due to many reasons and this might lead to irresponsible financial behaviour. Another issue here is what are the factors that contributed to an individual that does not performed financial management that leads to unpaid debt.